On the thermoeconomic and LCA methods for waste and fuel allocation in multiproduct systems. (15th May 2017) - da Silva, Julio Augusto Mendes; Santos, José Joaquim Conceição Soares; Carvalho, Monica; de Oliveira, Silvio
Abstract: The search for more efficient processes is mandatory in current society to save resources and avoid further environmental damages. Life Cycle Assessment, LCA, has become an important tool in evaluating the waste generated and resources necessary to produce a given product so that it can be compared with alternative products from energy and environmental points of view. In multiproduct energy systems, the allocation of resources and waste by methods traditionally utilized in LCA studies seems arbitrary. Thermoeconomic theories are well known for the rational allocation of waste and resources in multiproduct plants. This paper compares five allocation techniques usually applied in LCA studies with three thermoeconomic allocation techniques for pollutants (CO2, NOx and SOx ) and resources (fuel consumption). The comparison revealed that commonly applied methods for the allocation of emissions in LCA studies provided wide variation between results (over 88%). Thermoeconomic methods, in turn, provided less variation and yielded a more rational approach as the multiproduct step was disaggregated into its subsystems. Thermoeconomic approaches seem to be a perfect match to LCA when multiproduct systems have to be considered. Thus, merging thermoeconomics and LCA methodologies provides a deeper and more rational perspective for complex systems via an integrated analysis. Highlights: The manuscript compared eight allocation techniques for fuel and emissions. Five allocation techniques applied in LCA vs. three thermoeconomic methods. Thermoeconomic methods provided less variation and yielded a more rational approach. An argument is made for merging thermoeconomics and LCA methodologies. Global perspective of a complex system via integrated analysis can be provided.